Application of hygienic and sanitary standards for cookware against food quality - Louisa Nicolina Kandoli (Journal of Advanced Research in Social Sciences and Humanities, 2022)
Aim: This study aimed to investigate the relationship between the hygienic and sanitary standards applied to cooking utensils and the quality of the food produced. Methodology: The methodology was descriptive and qualitative, and the data came from previously published scientific articles and journals. Findings: According to the research results, various materials, including metal, stainless steel, wood, and Glass, are suitable for cooking utensils. Stainless steel is the most sanitary and hygienic standard because it does not rust and is simple to clean, meaning it will not pollute the body or leave behind any microbes or pathogens. Glass is another material generally accepted as safe. However, its fragility makes it vulnerable to breakage. Implications/Novel Contribution: Cooking utensils can be considered the most important component used in food processing and will affect the overall quality of the food served. As a result, it is necessary to discuss and explain further related to the hygienic and sanitary standards application of cooking utensils to food quality. Both the findings and the subsequent discussion of this research will improve the overall quality of the food.